1997
DOI: 10.1038/bjc.1997.529
|View full text |Cite
|
Sign up to set email alerts
|

5-Ethynyluracil (GW776): effects on the formation of the toxic catabolites of 5-fluorouracil, fluoroacetate and fluorohydroxypropionic acid in the isolated perfused rat liver model

Abstract: Summary We studied the effects of 5-ethynyluracil (GW776), a potent inactivator of dihydropyrimidine dehydrogenase, on the metabolism of 5-fluorouracil (5-FU), in particular with respect to formation of the toxic compounds fluoroacetate (FAC) and 2-fluoro-3-hydroxypropionic acid (FHPA), using fluorine-19 nuclear magnetic resonance and the isolated perfused rat liver model. Livers were perfused with 5-FU alone at a dose of 15 mg kg-' body weight or with 5-FU + GW776 at doses of 15 mg 5-FU kg-' body weight and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…As FHPA and FAC were not detectable in the non-concentrated perfusates, we determined their concentrations from the spectra of the concentrated perfusates. It should be noted that the amounts of FHPA and FAC were underestimated as demonstrated previously (Arellano et al, 1997). Table 2 shows the results of the IPRL experiments.…”
Section: Quantitative Analysissupporting
confidence: 54%
“…As FHPA and FAC were not detectable in the non-concentrated perfusates, we determined their concentrations from the spectra of the concentrated perfusates. It should be noted that the amounts of FHPA and FAC were underestimated as demonstrated previously (Arellano et al, 1997). Table 2 shows the results of the IPRL experiments.…”
Section: Quantitative Analysissupporting
confidence: 54%
“…26,27 Because the patterns of toxicity development clearly differ between DIF preparations and non-DIF preprations, 28-31 the possibility cannot be denied that control or inhibition of DPD decreases the degradation products and decreases toxicity. [32][33][34][35] Relation between DPD and sensitivity to 5-FU It is well known that thymidylate synthase (TS), a target enzyme of 5-FU, affects the sensitivity of 5-FU. [36][37][38] It is also reported that DPD determines 5-FU sensitivity.…”
Section: Toxicity Caused By 5-fu Catabolitesmentioning
confidence: 99%
“…A higher cytidine deaminase activity in humans (Ho, 1973) combined with an enhancement of the thymidine phosphorylase level in tumor tissue (Miwa et al, 1998) could account for the high formation of 5-FU and catabolites observed in human urine. It should be pointed out that CAP, as 5-FU (Lemaire et al, 1996;Arellano et al, 1997), leads to the formation of low amounts of two FBAL metabolites, FHPA and FAC, even in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Male Wistar rats (Iffa Credo, Lyon, France) were used. The IPRL experiments have been described previously (Arellano et al, 1997). CAP was injected into the perfusate after 1 h of liver equilibration, and the experiments were continued for 3 h. At the end of the experiments (n ϭ 5), the perfusate was freeze-dried, stored at Ϫ80°C, and resuspended in H 2 O to a known volume close to 3 ml immediately before 19 F NMR analysis.…”
Section: Methodsmentioning
confidence: 99%